2016
DOI: 10.1007/s11096-016-0357-7
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the cost-effectiveness of pharmacist-managed anticoagulation service for older adults with atrial fibrillation in Singapore

Abstract: Background Oral anticoagulation with warfarin is the cornerstone therapy in atrial fibrillation (AF) for stroke prevention. Multi-disciplinary anticoagulation management services have been shown to be cost-effective in the United States, Hong Kong and Thailand, but the findings are not readily generalizable to Singapore's healthcare system. Objective This study aimed to evaluate the cost-effectiveness of pharmacist-managed anticoagulation clinic (ACC) compared with usual care (UC) for the management of older a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…Subanalyses of the large comparative trials have demonstrated warfarin control of around 75% TTR in Australia and 65% TTR in Singapore. (12,16) Outside of these trials, the limited data on warfarin control in these countries have reported similar results with TTRs between 55%(17) and 81%(18) in Australia, and between 58% (19) and 65% (20) in Singapore. Wang et al (21) suggested the differential effects in warfarin control seen between Asians and non-Asians may be influenced by genetic polymorphisms, but also affected by demographic differences including body weight and renal function.…”
Section: Introductionmentioning
confidence: 71%
“…Subanalyses of the large comparative trials have demonstrated warfarin control of around 75% TTR in Australia and 65% TTR in Singapore. (12,16) Outside of these trials, the limited data on warfarin control in these countries have reported similar results with TTRs between 55%(17) and 81%(18) in Australia, and between 58% (19) and 65% (20) in Singapore. Wang et al (21) suggested the differential effects in warfarin control seen between Asians and non-Asians may be influenced by genetic polymorphisms, but also affected by demographic differences including body weight and renal function.…”
Section: Introductionmentioning
confidence: 71%
“…Patients with AF were selected as they contribute to the bulk of the patient load at NUH. Exclusion criteria included: (1) Patients who switched between the two models of consultation within the study period, (2) Patients who were taking warfarin for other indications, especially for active clots such as heart thrombus or pulmonary embolism as these patients might cease warfarin therapy over the 6 months follow-up period, and…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Numerous studies have shown that pharmacist-managed anticoagulation clinics (ACC) are more effective and less costly compared with usual care. [1][2][3][4][5][6][7][8] However, in terms of time requirements for patient visits to ACC, a study reported that a substantial amount of time, averaging 2.5 hours per visit and 40 hours per year, was spent on waiting time and travel. 9 At National University Hospital (NUH) in Singapore, ACC clinics have a monthly load of more than 1000 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pored navedenih opservacionih studija, sprovedene su i farmakoekonomske evaluacije zasnovane na modelovanju dugoročnog uticaja menadžmenta antikoagulantne terapije varfarinom od strane farmaceuta na nivou hipotetičke kohorte [30,31]. Studija sprovedena u Singapuru od strane Chua i sar.…”
Section: Diskusijaunclassified
“…Studija sprovedena u Singapuru od strane Chua i sar. [30], imala je za cilj procenu troškovne isplativosti pružanja FZZ pacijentima na varfarinu sa indikacijom atrijalne fibrilacije, a iz perspektive pacijenta i finansirajuće institucije (3 rd party payer). Kreiran je Markovljev model sa tromesečnom dužinom ciklusa i tridesetogodišnjim vremenskim horizontom, pri čemu je vršeno poređenje troškova i humanističkih ishoda, izraženih kao godina života korigovana za kvalitet (Quality-adjusted life year-QALY).…”
Section: Diskusijaunclassified